Acute Renal Infection in Adult, Part 2: Emphysematous Urinary Tract Infection—What the Radiologist Needs to Know - Hazarika, Suman; Venkataramanan, Rochita; Das, Tonmoy; Venkataramanan, Akash; Deuri, Sukanya; Lohchab, Shalini; Rongpipi, Tamsir; Agarwala, Ashish (Journal of Gastrointestinal and Abdominal Radiology, 2020)
Renal emphysema, as described by Kelly and MacCallum in 1898, refers to the spontaneous generation of gas within the renal parenchyma and surrounding tissues. Since its initial description, it has become apparent that the spectrum of radiologically visible renal and perirenal gas includes three distinct clinical entities: (1) emphysematous pyelonephritis, a necrotizing infection associated with gas formation in the renal parenchyma, (2) emphysematous pyelitis, in which gas is confined to the renal pelvis and calyces, and (3) gas-forming perinephric abscess. In this article, we will review gas-forming infections of the urinary system in terms of radiological features, clinical manifestations, predisposing factors, and appropriate management guidelines.
Keywords: emphysematous cystitis; emphysematous pyelonephritis; urinary infection